AKULTURASI AGAMA DAN BUDAYA DALAM TRADISI LARANGAN PERNIKAHAN SATU MARGA - Yuwita, Rahmi (UIN Sumatera Utara Medan, 2024)
Religion and culture are two things that cannot be separated from people's lives, both of which play an important role in managing the social life of the community. However, it is undeniable that sometimes religion and culture also become a problem that always involves tension and this is very difficult to avoid. Such as the issue of the tradition of prohibiting the marriage of one clan in the Batak tribe, where religion allows the type of marriage of one clan, but in the custom of marriage it is strictly prohibited, even forbidden in Batak customs. This research was conducted to find out how religious law and customary law regarding the tradition of prohibiting marriages that occur in North Padang Lawas Utara, and this type of research is a qualitative research that is classified as field research involving interviews with informants, and this study uses an empirical juridical approach, where the researcher goes directly to the field to find out the applicable legal provisions and what has happened in people's lives. And as supporting literature in this study also use books, journals or others that are in accordance with the title of this research. The results showed that the marriage of one clan in North Padang Lawas Utara had undergone changes. Initially, the type of marriage applied was exogamous and endogamous marriage, but for now some people have changed it to eleutrogamy type marriage. This change is caused by several factors and the strongest factors are religious factors and love factors. Some people now prioritize religious law rather than customary law in the tradition of prohibiting the marriage of one clan